Testing Learning Media for English Learning Applications Using BlackBox Testing Based on Equivalence Partitions - Dwi Yulistyanti; Tri Yani Akhirina; Thomas Afrizal; Aulia Paramita; Naely Farkhatin (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
Some testings or testings of an application are very important. So that an application can appear to be running properly or there are still errors in its use. Which later can be improved optimally. In this test, the black box testing technique was used as a test. Black box testing is a system for testing an application by looking at the menu whether it is following what is desired or still needs improvement. The application that will be tested is the Duolingo application which on the play store gets a high rating and is used by more than 12 million smartphone users. The type of testing of the method used, namely the black box, varies, but one of the methods used here is Equivalence Partitions. The Equivalence Partitions technique is a test based on entering data on each form of the system or application used. In each menu, input data on each form will be tested and carried out based on its function, whether it is valid or not. So that by doing this testing the application is getting better and the application must be of good quality according to their respective functions. So that many smartphone users who want to use the application make it easy to use it